2013
DOI: 10.1080/03235408.2013.824640
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the host response of lowland and upland rice varieties from Myanmar to the rice root-knot nematodeMeloidogyne graminicola

Abstract: The rice root-knot nematode Meloidogyne graminicola is considered one of the most potentially important nematode pathogens of rice, especially in South and Southeast Asia, in a range of rice production systems. Identification of M. graminicola-resistant or -tolerant rice varieties will enable breeding programmes to develop rice varieties which are able to limit yield losses caused by this nematode species. The host response to M. graminicola infection of 15 lowland rice varieties and 9 upland rice varieties, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…This reduction in dry weight of plant parts might be due to more diversion of food, nutrients for the feeding of nematode thus causing remarkable reduction in growth and development of all plant parts. The similar finding was also reported by Khan et al (2012) and Win et al (2013). The percentage of partitioning of shoot and root presented in Table 2 showed that there was not so much difference between inoculated and uninoculated plants.…”
Section: Resultssupporting
confidence: 90%
“…This reduction in dry weight of plant parts might be due to more diversion of food, nutrients for the feeding of nematode thus causing remarkable reduction in growth and development of all plant parts. The similar finding was also reported by Khan et al (2012) and Win et al (2013). The percentage of partitioning of shoot and root presented in Table 2 showed that there was not so much difference between inoculated and uninoculated plants.…”
Section: Resultssupporting
confidence: 90%
“…The objective of our study was to evaluate the host suitability of selected cultivated plants, which are commonly grown or could be grown in rotation with Asian rice (Oryza sativa L.) in both lowland and upland rice-based agro-ecosystems in Myanmar where M. graminicola is omnipresent (Win et al 2011). Our study was also prompted by the observations that although upland Asian rice cultivars are susceptible to M. graminicola infection as lowland Asian rice cultivars, the occurrence of M. graminicola was low in the upland rice-based agro-ecosystems in Myanmar where rice is being grown in rotation with a variety of crops such as blackgram (Vigna mungo L.) and chickpea (Cicer arietinum L.) (Win et al 2011(Win et al , 2013(Win et al , 2015.…”
Section: Introductionmentioning
confidence: 92%
“…Relatively few studies have been published on the host response of rice germplasm to M. graminicola infection. Most of these studies were conducted either in pots filled with soil in a glasshouse, in outdoor raised beds filled with soil or under field conditions (Plowright et al 1999;Soriano et al 1999;Pokharel et al 2011;De Waele et al 2013;Win et al 2013). All these methods allow the evaluation of both susceptibility/resistance to M. graminicola reproduction and sensitivity/tolerance to damage caused by M. graminicola, but all these methods also require a lot of space and time, and high inputs labour-wise and money-wise.…”
Section: Introductionmentioning
confidence: 99%